UN Resolution 16/18: An Attempt to Reconstruct the Indistinctness of the Blasphemy Law in Religious Life in Contemporary Indonesia - Abd. Rasyid; Wasil Wasil (ILMU USHULUDDIN, 2023)
The purpose of this article is to describe the vagueness of the concepts and the negative effects of the Blasphemy Law, which is operated in contemporary Indonesia with the law No. 1/PNPS/1965. Since its enactment in 1965, this law has been used by various intolerant groups to vilify, to discredit and to discriminate minority communities, including indigenous people, aliran kepercayaan groups (often used interchangeably with aliran kebatinan or Kejawen), and other non-conformist groups as deviant. According to the Blasphemy Law contents, opethese groups are not recognized as official religions because their religious doctrines are not allowed to be practiced and contradict those held by the majority. This article argues that the maintenance of the Blasphemy Law in Indonesia is not only detrimental to interfaith relations and harmony among the country’s diverse religious communities, but also contributes to the high number of violations of religious freedom and belief. Furthermore, a lot of researchers measure that the blasphemy law is one of two major problems in Indonesia — the other problems are related with religious conversion and proselytism. Its repeal is essential to promote religious tolerance and respect for individual beliefs. Certain doctrines are accepted on the basis of majority rather than merit, while those of minorities are often disregarded. Alternatively, this article will consider Resolution 16/18, also called “Combating Intolerance, Negative Stereotyping and Stigmatization of, and Discrimination, Incitement to Violence against Persons Based on Religion or Belief,” which was submitted by the Organisation of Islamic Cooperation (OIC) countries to the UN Human Rights Council in 2011 to address the problems caused by the controversial blasphemy law. Keywords: Blasphemy Law, Religious Freedom, and UN Resolution 16/18.